Exploring the Regulation Mechanism of miRNAs Transcription Using Genomic and Epigenetic Functional Annotations - Xie, Lihua; Liu, Chun; Yang, Honghui; Lin, Hua; Sun, Shenghua (Current Bioinformatics, 2014)
Uncovering the transcriptional regulation mechanism of mammalian miRNAs is crucial to understand the role of these tiny regulators in cellular processes. Based on 1,030 genomic and epigenetic functional annotations, we compared these features of regulatory regions between miRNAs and protein-coding genes. Support vector machine (SVM) was used to quantify the contribution of each annotation group or group combination in distinguishing miRNA regulatory regions. We observed fewer repetitive DNA elements and SNPs, but more intensive DNA methylation in the miRNA regulatory regions. On the contrary, there are more predicted CpG islands and higher H3K9me1 levels in the regulatory regions of protein-coding genes. This analysis indicated that epigenetic factors such as DNA methylation and specific histone marks are the most informative groups, suggesting epigenetic events may play a more important role in miRNA transcription than previously thought. Furthermore, these results also revealed the interactive effects among various genomic or epigenetic factors involved in miRNA transcription.
Keywords: Epigenetics